A REVISION OF PLATANTHERA (ORCHIDACEAE; ORCHIDOIDEAE; ORCHIDEAE) IN ASIA - Efimov, Petr G. (Phytotaxa, 2016)
A revision of Platanthera of Asia is presented, which recognises 78 species. Each species description is supplemented by extensive synonymy and a distribution map; all species are illustrated by line drawings. In the general chapters, special importance is given to delineating the generic limit of Platanthera, which is continuously changing. An improved taxonomic system of Platanthera on a global scale is elaborated in connection with existing phylogenetic studies and discussed in detail. The genus is subdivided into five subgenera, two of which are further divided into sections. The possible main routes of transcontinental migrations during the evolution of the genus are speculated upon in a section on ‘biogeographic considerations’. One new species (P. miniangustata), 12 new subgenera and sections, five new combinations at specific and intraspecific ranks and 20 new neo- and lectotypes are included.